TREATMENT OF DYSLIPIDEMIA: PCSK-9 IN FOCUS - Singh Lukac, Sandra; Popovic, Ljiljana; Rasulic, Iva; Petakov, Ana; Bogdanovic, Jelena; Mitrovic, Marija; Krstic, Milica; Lalic, Katarina (Medical Research, 2025)
Cardiovascular disease is the leading cause of death worldwide, accounting for one-third of all global mortality. Dyslipidemia is one of the most common risk factors and plays a cardinal role in the development and progression of atherosclerotic cardiovascular disease. Since statin therapy is often not sufficient or despite achieving target values, cardiovascular disease is still occurring, todays focus is on new therapeutic options with significantly more potent effects. The reduction in LDL cholesterol levels with PCSK-9 inhibitors is about 60% when used as monotherapy and as much as 85% when combined with high-intensity statins and/or other lipid-lowering therapies. Alirocumab and evolocumab are two monoclonal antibodies that effectively bind to the LDL receptor, interfering with its degradation. Inclisiran is a small interfering RNA that interferes with the synthesis of PCSK-9 molecules and effectively reduces LDL-C. Indications for PCSK-9 inhibitors use are increasingly expanding due to the discovery of their pleiotropic effects. Also, the focus is on discovering new mechanisms of PCSK-9 inhibition that would open the door to the development of new therapeutic agents. Studies of the efficacy and safety of oral PCSK-9 are ongoing, as well as early stages of clinical trials of gene editing strategies to treat dyslipidemias. The purpose of this review article is to provide an overview of the current knowledge on the application of PCSK-9 inhibitors.